An essential role of the reversible electron-bifurcating hydrogenase Hnd for ethanol oxidation in Solidesulfovibrio fructosivorans - Kpebe, Arlette; Guendon, Chloé; Payne, Natalie; Ros, Julien; Khelil Berbar, Manel; Lebrun, Régine; Baffert, Carole; Shintu, Laetitia; Brugna, Myriam (Frontiers in Microbiology, 2023)
The tetrameric cytoplasmic FeFe hydrogenase Hnd from Solidesulfovibrio fructosivorans (formely Desulfovibrio fructosovorans) catalyses H2 oxidation and couples the exergonic reduction of NAD+ to the endergonic reduction of a ferredoxin by using a flavin-based electron-bifurcating mechanism. Regarding its implication in the bacterial physiology, we previously showed that Hnd is involved in a non-essential role in ethanol metabolism when bacteria grow fermentatively on pyruvate. Under these conditions, it consumes H2 to produce reducing equivalents for ethanol production as a fermentative product. In this study, the approach implemented was to compare the two S. fructosivorans WT and the hndD deletion mutant strains when grown on ethanol as the sole carbon and energy source. Based on the determination of bacterial growth, metabolite consumption and production, gene expression followed by RT-q-PCR, and Hnd protein level followed by mass spectrometry, our results confirm the role of Hnd hydrogenase in the ethanol metabolism and furthermore uncover for the first time an essential function for a Desulfovibrio hydrogenase. Hnd is unequivocally required for S. fructosivorans growth on ethanol, and we propose that it produces H2 from NADH and reduced ferredoxin generated by an alcohol dehydrogenase and an aldehyde ferredoxin oxidoreductase catalyzing the conversion of ethanol into acetate. The produced H2 is then used for sulfate reduction. Hnd is thus a reversible hydrogenase that operates in H2-consumption by an electron-bifurcating mechanism during pyruvate fermentation and in H2-production by an electron-confurcating mechanism when the bacterium uses ethanol as electron donor.